The Effect of Solvency Ratio and Profitability on The Financial Performance of PT Charoen Pokphand Indonesia Tbk - Aprilyani, Tanti; Hidayat, Rahmat; Kusworo, Ahmad Dzulfikri Budi (Journal of Advances in Accounting, Economics, and Management, 2024)
The purpose of this study is to effect solvency ratio and profitability on financial performance of PT Charoen Pokphand Indonesia Tbk. Descriptive research using a qualitative approach is the type of research used in this study. Based on the results of the study, the financial performance of PT Charoen Pokphand Indonesia Tbk during the period 2021 to 2023 illustrates extraordinary achievements in terms of profitability, efficiency of asset use, and debt management. During the period, the company managed to increase its net profit margin from 10% to 40%, indicating excellent financial performance. Return on Assets (ROA) increased from 7% to 34%, indicating improved efficiency in asset use. The suggestion proposed is to continue to monitor and improve the efficiency of asset use, as well as consider investments that can increase asset returns. Return on Equity (ROE) also experienced a significant increase from 8% to 42%, demonstrating the company's ability to generate high returns on equity.